Kalāma Sulatāna Bāhū - Camana, S̱āha (Cetanā Prakāshana, 2009)
Study on the works of Sultān Bāhū, 1630-1691, Panjabi Sufi poet; includes his brief life introduction
Includes bibliographical references (p. 135). - Panjabi in Gurmukhi-Schr
Keywords: Sult̤ān Bāhū 1630-1691